To the problem of oil-gas-bearing capacity of the pre-Cambrian basement - Lukin, A.E. (Reports of the National Academy of Sciences of Ukraine, 2020)
Discovery of the group of fields with oil, gas-condensate, gas, and heterophase pools in the pre-Cambrian ba sement of the northern edge of the Dnieper-Donets aulacogen (Khuhrynska-Yuliyivska-Gashinovska-Evgeniev ska zone) bears witness to a great petroleum potential of this non-traditional source of natural hydrocarbons. But the effective prospecting, exploration and development of this genetic type of fields must be based upon distinct concepts about factors of their formation. First and foremost, one should take account for the petroliferous specificity of crystalline rocks. Contrary to sedimentary lithosomes, the jet-injection mechanism of accumulation of hydrocarbons goes hand in hand with dilatancy processes and decomposition of primary solid basement rocks with unpermeable matrix. Presence of pine pollen grains supposedely (in all probability) of Upper Oligocene — Lower Miocene age testifies to the decompression (including tectonic-caisson effect) decompaction (with concurrent suction of hydrocarbons) at the Neotectonic stage. This allows one to determine the promising oilgas- targets and, at the same time, to take into account a wide distribution of hydrocarbon pools with reservoir pressures lower than hydrostatic pressures.